2002
DOI: 10.1530/eje.0.1470485
|View full text |Cite
|
Sign up to set email alerts
|

Molecular defects of the CYP21 gene in Spanish girls with isolated precocious pubarche

Abstract: Objective: To determine the frequency of mutant alleles in the CYP21 gene in Spanish girls presenting with precocious pubarche (PP) and to assess the relationships between genotype and endocrinemetabolic variables. Design: Fifty-three unrelated girls with a history of PP (14 prepubertal, 8 pubertal and 31 postmenarcheal) and 35 controls were studied. Methods: Genomic DNA was extracted from peripheral blood leukocytes. After selection against the pseudogen, an allele-specific PCR was used to identify 14 known m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
1
5
0
2
Order By: Relevance
“…These findings are in agreement with those reported by Ibanez et al [35], revealing that the presence of functional ovarian hyperandrogenism was not related to CYP21A2 carrier status. …”
Section: Discussionsupporting
confidence: 94%
“…These findings are in agreement with those reported by Ibanez et al [35], revealing that the presence of functional ovarian hyperandrogenism was not related to CYP21A2 carrier status. …”
Section: Discussionsupporting
confidence: 94%
“…Other studies have reported an incidence of approximately 30 % based on a search for known CYP21 mutations (22,28,29) . Potau et al studied 53 unrelated girls with a history of PP and 35 controls (28) . Thirteen PP girls and eight control girls were heterozygous for one of the mutations studied.…”
Section: Discussionmentioning
confidence: 99%
“…Potau et al studied 53 unrelated girls with a history of PP and 35 controls (28) . The frequency of the carrier status was similar between 25 % in PP and 23 % in control groups (28) . The frequency of the carrier status was similar between 25 % in PP and 23 % in control groups (28) .…”
Section: Discussionmentioning
confidence: 99%
“…Esta proporción es más baja que en otras series de países como Grecia: 45,8% 39 , Brasil: 21,4% 40 , EE.UU. de Norteamérica: 30% 41 , y España; 25% 42 , pero más alta comparada con una serie italiana: 5,8% 43 . Es importante destacar que esas diferentes proporciones pueden deberse al uso de diferentes métodos y criterios para definir el diagnóstico (bioquímico, genético e incluso el estado de portador).…”
Section: N V E S T I G a C I ó Nunclassified